Praktik Governmentality dan Nativisme dalam Kebijakan Keluarga Berencana Krama Bali - Sukmaning Wahyu, I Putu Rai; Erawan, I Ketut Putra; Jayanthi Mertha, A.A Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2021)
ABSTRACT There is an odd relation between othering practices, efforts to secure native interests, birth control mechanism by introducing ‘four-child norm,’ and claim to preserve traditional Balinese naming system around the issuance of Krama Bali Family Planning policy. This article aims to explain the relation and historicity of these problems. To achieve these objectives, this study uses two theoretical perspectives: governmentality and nativism. The first perspective serves to investigate specific rationality behind the issuance of Krama Bali Family Planning policy and understand it as a way for the government to manufacture the governable subject; while the second perspective is used to analyze how the governable subjects are formed through the categorization of natives (orang ‘asli’ Bali) and non-natives (pendatang) groups. Keywords: governmentality, nativism, family planning, krama Bali